2016
DOI: 10.1111/1744-7917.12296
|View full text |Cite
|
Sign up to set email alerts
|

Further insight into reproductive incompatibility between putative cryptic species of the Bemisia tabaci whitefly complex

Abstract: The whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), with its global distribution and extensive genetic diversity, is now known to be a complex of over 35 cryptic species. However, a satisfactory resolution of the systematics of this species complex is yet to be achieved. Here, we designed experiments to examine reproductive compatibility among species with different levels of mitochondrial cytochrome oxidase I (mtCOI) divergence. The data show that putative species with mtCOI divergence of >8% be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…tabaci species complex members. Though few controversies did occur [65,66], reclassification based on the 3.5% and 4% genetic divergence revealed that 42 groups are clearly distinct (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…tabaci species complex members. Though few controversies did occur [65,66], reclassification based on the 3.5% and 4% genetic divergence revealed that 42 groups are clearly distinct (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns were further confirmed by an ABBA-BABA test which identified signatures of introgression between MEAM1 and IO confirming previous studies reporting gene flow between IO and MEAM1 in the field in Réunion Island [ 62 ]. Furthermore, evidence of incomplete mating isolation among the more closely related members of the complex where mtCOI diverge by ≤ 7% has been repeatedly demonstrated [ 63 , 64 ]. Our results also show evidence of introgression between IO and MED in Réunion Island which had not been detected previously through the use of microsatellite DNA markers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dinsdale et al (2010) proposed a general threshold of 3.5% for mitochondrial cytochrome oxidase I (mtCOI) DNA sequence divergence for species delimitation, which currently leads to the identification of at least 35 distinct species assigned to~11 major clades (Barbosa et al, 2014;Hu et al, 2014). With few minor nonconclusive exceptions, reproductive compatibilities' experiments confirm so far the accuracy of the cryptic species concept adding credibility to the mtCOI approach (Liu et al, 2012;Qin, Pan, & Liu, 2016).…”
Section: Introductionmentioning
confidence: 97%